Population status and distribution of Rhesus Macaque, Macaca mulatta, in a moist deciduous forest of Bangladesh (Bangladesh Journal of Zoology, 2016)
A study was conducted on population status and distribution of Rhesus Macaque, Macaca mulatta, in moist deciduous forest of Bangladesh from April to October 2015. Observation was carried out in the Madhupur deciduous forest, Tangail. In total, 248 individuals belonging to 11 groups were recorded. The group size ranged from 9 to 51 (mean 22.54 ± 11.68) individuals. Among the total population, 48.5% were adults and 51.5% immature animals (sub-adult male, sub-adult female, juvenile and infant). The ratio of adult and immature was 1 : 1.85 and the sex ratio of adult male and female was 1 : 1.49. The groups were 0.77 to 7.47 km (mean 2.5 km ± 2.2, n = 11) apart from each other.Bangladesh J. Zool. 44(1): 61-72, 2016